First-person narratives around sexuality in residential healthcare settings: a meta-ethnographic synthesis - Hooper, Anna; De Boos, Daniella; das Nair, Roshan; Moghaddam, Nima Golijani (Taylor & Francis, 2016)
The aim of this review is to identify, critically appraise, and synthesise the existing literature exploring adults’ narratives around sexuality within residential healthcare settings from a first-person perspective. A systematic literature review was undertaken. Six databases were searched. A meta-ethnographic approach was used to synthesise studies’ findings. Thirteen studies using qualitative methodology that met the inclusion criteria were identified. The synthesis revealed six key themes: how service users define sexuality, sexuality as something not to be discussed (“privates are private”), sexuality as a separate aspect of the self (“sectionality”), hopes and fears for the future, the impact of the environment (“physicality of being physical”), and adapted sexuality. The studies included were of varying quality. Sexuality remains an important aspect for many residents, yet is rarely noted or discussed with them by healthcare staff. The residential healthcare environment presents implicit and explicit barriers to sexuality expression, causing residents to adapt how they experience their sexuality. Findings from this review highlight the importance of considering service users’ perspectives, and the need for open communication between residents and practitioners to facilitate care provision that acknowledges the barriers of the environment on sexuality and considers the person beyond the presenting illness.